Aerobic oxidation of secondary alcohols in water with ABNO/tert-butyl nitrite/KPF6 catalytic system. Issue 7 (15th February 2017) - Ma, Jiaqi; Hong, Chao; Wan, Yan; Li, Meichao; Hu, Xinquan; Mo, Weimin; Hu, Baoxiang; Sun, Nan; Jin, Liqun; Shen, Zhenlu
Graphical abstract: A green and efficient transition-metal free ABNO/ tert -butyl nitrite/KPF6 -catalyzed aerobic oxidation of secondary alcohols in water has been achieved. Under the optimal reaction conditions, a number of secondary aliphatic alcohols and secondary benzylic alcohols can be converted to their corresponding ketones in excellent yields (up to 99%). Highlights: Oxidation of secondary alcohols into ketones. ABNO, tert -butyl nitrite and KPF6 as the catalysts and oxygen as the oxidant. Good to excellent yields can be obtained. Water as the green reaction solvent. Metal-free reaction conditions. Abstract: A green and efficient transition-metal free ABNO/ tert -butyl nitrite/KPF6 -catalyzed aerobic oxidation of secondary alcohols in water has been achieved. Under the optimal reaction conditions, a number of secondary aliphatic alcohols and secondary benzylic alcohols can be converted to their corresponding ketones in excellent yields (up to 99%).